"We have already heard that the treatment doesn't do anything, so why should we take it?": A mixed method perspective on Chagas disease knowledge, attitudes, prevention, and treatment behaviour in the Bolivian Chaco. - Sandra Parisi; Miriam Navarro; Jeremy Douglas Du Plessis; Jonathan Phillip Shock; Boris Apodaca Michel; Minerva Lucuy Espinoza; Carolina Terán; Nino Antonio Calizaya Tapia; Katharina Oltmanns; Abundio Baptista Mora; Claudia Saveedra Irala; Angel Alberto Rivera Rojas; et al. (Public Library of Science (PLoS), 2020)
Background Chagas disease (CD) is highly endemic in the Bolivian Chaco. The municipality of Monteagudo has been targeted by national interventions as well as by Médecins Sans Frontières to reduce infection rates, and to decentralize early diagnosis and treatment. This study seeks to determine the knowledge and attitudes of a population with increased awareness and to identify remaining factors and barriers for sustained vector control, health care seeking behaviour, and access, in order to improve future interventions. Methodology/principal findings A cross-sectional survey was conducted among approximately 10% (n = 669) of the municipality of Monteagudo's households that were randomly selected. Additionally, a total of 14 in-depth interviews and 2 focus group discussions were conducted with patients and key informants. Several attitudes and practices were identified that could undermine effective control against (re-)infection. Knowledge of clinical symptoms and secondary prevention was limited, and revealed specific misconceptions. Although 76% of the participants had been tested for CD, only 18% of those who tested positive concluded treatment with benznidazole (BNZ). Sustained positive serologies after treatment led to perceived ineffectiveness of BNZ. Moreover, access barriers such as direct as well as indirect costs, BNZ stock-outs and a fear of adverse reactions triggered by other community members made patients opt for alternative treatments against CD such as veterinary ivermectin, used by 28% of infected participants in our study. The lack of accessible care for chronic complications as well as socioeconomic consequences, such as the exclusion from both job opportunities and bank loans contributed to the ongoing burden of CD. Conclusions/significance Large scale interventions should be accompanied by operational research in order to identify misconceptions and unintended consequences early on, to generate accessible data for future interventions, and for rigorous evaluation. An integrated, community-based approach tackling social determinants and including both traditional and animal health sectors might help to overcome current barriers and advocate for patients' rights.